How can the effect of particle surface roughness on the contact area be predicted? - Nadimi, Sadegh; Angelidakis, Vasileios; Otsubo, Masahide; Ghanbarzadeh, Ali (Computers and Geotechnics, 2022)
This paper describes a systematic study of the effect of fractal rough surfaces on the contact area with the aim of advancing contact constitutive laws used in the Discrete Element Method. An in-house Boundary Element code is adopted to investigate the mechanical behaviour of computer-generated surface roughness. Surfaces are generated to have methodically controlled root mean square height (S-q), root mean square gradient (S-dq), short wavevector (q0), large wavevector (q(1)), Hurst exponent (H) and fractal dimension (D-f). The effect of each parameter on the contact area is investigated. Two recently proposed analytical solutions in tribology (i.e. Persson-Tosatti and Pastewka-Robbins) are applied to predict the real contact area. A parameter based on S-q, q(0), and H is proposed and its sensitivity for real contact area prediction is demonstrated. Surfaces of natural sand are simulated and their mechanical response shows similar trend as the computer-generated surfaces, albeit more complex.
Keywords: Particle -scale behaviour; Surface roughness; Contact law; Friction